El jefe de calidad y sus funciones en la empresa cartonera Palmaplast. - Gomez Castro, Lisseth Carolina (My University, 2018)
The process of formation of the quality of the products in the conditions of the contemporary industrial production, constitutes an unstable process, subjected to the perturbations given by the heterogeneity of the properties of the materials and compounds obtained in the technological stages of the processes, the violation of the technological discipline and the deterioration of the facilities and the instruments of measurement and control, which causes the variability of the parameters and indices of quality of the production. The main aspects of product quality management start with the performance, reliability and durability of the product. With quality management programs, the manufactured products are tested to verify that they work in accordance with their promises or declared characteristics. The methodology applied in the research work is descriptive, the main characteristic of this type of study is the description of the fact subject of research; the research will not only be devoted to data collection, but also to the prediction and identification of the variables. The research is also in situ, because it will be carried out in the place where the object of study is located.
El proceso de formación de la calidad de los productos en las condiciones de la producción industrial contemporánea, constituye un proceso inestable, sometido a las perturbaciones dadas por la heterogeneidad de las propiedades de los materiales y compuestos obtenidos en las etapas tecnológicas de los procesos, la violación de la disciplina tecnológica y el deterioro de las instalaciones y los instrumentos de medición y control, lo que provoca la variabilidad de los parámetros e índices de calidad de la producción. Los aspectos principales de la gestión de la calidad del producto comienzan con el rendimiento, la fiabilidad y la durabilidad del producto. Con los programas de gestión de la calidad, los productos fabricados se someten a pruebas para verificar que funcionan de acuerdo con sus promesas o características declaradas. La metodología aplicada en el trabajo de investigación es de tipo descriptivo, la característica principal de este tipo de estudio es la descripción del hecho sujeto de investigación; la investigación no solo se dedicará a la recolección de datos, sino que también a la predicción y a la identificación de las variables. La investigación también es in situ, debido a que se realizará en el sitito donde se encuentra el objeto de estudio.
Keywords: CALIDAD; CONTROL; EFICIENCIA; ORGANIZACIÓN; GESTIÓN DE CALIDAD